ENSURING SAFETY AND PROTECTION OF PERSONAL DATA ON THE INTERNET: ISSUES OF SELECTION OF OPTIMAL RESEARCH METHODOLOGY - Bissaliyev, Marlen; Shakirov, Karimzhan (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
This article explores the methodologies and legal challenges associated with personal data protection within the global information space. We examine the limitations of relying solely on specialized research methods and techniques. We argue that personal data protection issues require a more comprehensive, multidisciplinary methodological approach. The primary goal is to analyze the selected methodological strategies and evaluate their effectiveness. We analyze a philosophical framework that seeks to deepen the understanding of personal data protection issues, addressing legal and ethical dimensions. We aim to contribute to the broader discourse on data security and privacy through various lenses, including legal, technological, and philosophical perspectives. The study focuses on four analytical methods for developing legal technologies to protect personal data internationally. A systematic analysis of personal data as a legal phenomenon, functional analysis within the framework of legal regulation, sociological and psychological approach, and axiological analysis to understand the meaning and evolution of personal data protection rights. These approaches aim to create a unified concept of legal technology for personal data protection, which makes it possible to identify new types of data, study the components of legal technology in detail, and increase the efficiency of legal regulation.